IMPLEMENTASI KEBIJAKAN PENGELOLAAN DANAU LIMBOTO - Rifkah S. Akibu (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2017)
This study aimed to look at the implementation of the Policy Management Limboto Lake, Lake Limboto is an area that the quality of the environment is strongly influenced by the development activities undertaken by the two regencies / cities, namely Gorontalo regency and city of Gorontalo, the formulation masaalahnya is 1) how policy implementation regulations management Limboto Lake , 2) Strategy and the concept of what should be done by the government in the implementation of the management of lake Limboto. Thus, efforts to mengimpelentasikan management Limboto Lake is (1) the restoration of Lake Limboto, (2) the use of Lake Limboto and (3) preservation of Lake Limboto should be carried out by (1) based citizens DAS Limboto (not just residents of coastal lakes Limboto), (2) implemented collaborative management, and through (3) collective action locally. The earliest step to start it all is the delimitation of the Lake Limboto definitively. Indeed, this step is not easy and can trigger a